2006
DOI: 10.1007/s10876-005-0043-8
|View full text |Cite
|
Sign up to set email alerts
|

Energy-dependent Electrospray Ionisation Mass Spectrometry of Carbonyl Clusters

Abstract: 3 , P(OPh) 3 , P(OMe) 3 , PO 3 C 5 H 9 ) are described and the relative importance of carbonyl loss versus phosphine loss as a fragmentation pathway is assessed. Qualitatively, the phosphine ligands bind more strongly to Ir 4 (CO) 11 clusters than to Ru 6 C(CO) 16 . The influence on the collision cell pressure on MS/MS spectra of transition metal carbonyl cluster anions is also explored showing that a greater, simultaneous, distribution of fragment ions is produced as the collision cell pressure is increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 66 publications
3
11
0
Order By: Relevance
“…The corresponding cluster k values of the fragment should be on the increase. Very interesting extensive work on the metal carbonyls that involves stripping off the CO ligands has been done by several research groups (Butcher, et al, 2002(Butcher, et al, , 2003Crawford, et al, 2006;Critchley, et al, 1999;Dyson, et al, 2001;Henderson, et al, 1998Henderson, et al, , 2009 Table 7). Although the series and the skeletal numbers predict that each of the Re skeletal atoms except one should have a hydrogen atom, the structural determination indicates all the hydrogen atoms are bridging (Miessler, et al, 2014) as observed in borane clusters.…”
Section: Limits Of the Carbonyl Cluster Seriesmentioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding cluster k values of the fragment should be on the increase. Very interesting extensive work on the metal carbonyls that involves stripping off the CO ligands has been done by several research groups (Butcher, et al, 2002(Butcher, et al, , 2003Crawford, et al, 2006;Critchley, et al, 1999;Dyson, et al, 2001;Henderson, et al, 1998Henderson, et al, , 2009 Table 7). Although the series and the skeletal numbers predict that each of the Re skeletal atoms except one should have a hydrogen atom, the structural determination indicates all the hydrogen atoms are bridging (Miessler, et al, 2014) as observed in borane clusters.…”
Section: Limits Of the Carbonyl Cluster Seriesmentioning
confidence: 99%
“…These opposing processes are reflected in Tables 7 and 8. The removal of CO ligands from transition metal carbonyl clusters has been an intense field of research (Critchley, et al, 1999, Douglas, et al, 2001, Butcher, et al, 2002, 2003, Crawford, et al, 2006, Henderson, et al, 2009). The silicon clusters Si n (n=4-10) were theoretically studied (Slee, et al, 1989) (Hughes, et al, 2000).…”
Section: Capping and De-capping Seriesmentioning
confidence: 99%
“…Ru (Crawford et al, 2006); W (Thompson et al, 2003); Zn (Goicoechea & Sevov, 2006a) [M+L] -, X=halide,…”
Section: R=ch3 Etmentioning
confidence: 99%
“…As (Florencio et al, 1997); Cr and Fe (Martinez- Alvarez et al, 2004); Fe (Alley & Henderson, 2001;Tharamani et al, 2008); Ge (Jirásko et al, 2009;Lamb & Sweetman, 1996; Pt (Mastrorilli et al, 2004); Ru (Pelagatti et al, 2005); Sn (Baul et al, 2005a;Baul et al, 2005b;Baul et al, 2005c;Baul et al, 2006a;Baul et al, 2006d;Baul et al, 2007a;Baul et al, 2007b; [M+Na-2H] -Sn (Jirásko et al, 2007) [2M+X] -Fe (Henderson & Alley, 2002); Ru (Pelagatti et al, 2005); Sn (Baul et al, 2006d) [An] 2-Bi (Mlýnek & Dahl, 1997); Os (Dyson et al, 2000); Ru (Crawford et al, 2006) [M] -.…”
Section: Cf3so3 Complex Ligandmentioning
confidence: 99%
“…The complex, FeIr 4 (CO) 15 2¯ ( 1) and Fe 2 Ir 3 (CO) 14¯ ( 2) were found to have a trigonal bipyramid shapes but the former was more elongated in axial positions than the later 13 . The complex 1 has the cluster code M-5-7-76-A and 2 has the code M-5-9-72-C.…”
Section: Using the Cluster Table To Interpret Some Literature Workmentioning
confidence: 96%